Comparison of six-week flywheel and traditional resistance training on deceleration and dynamic balance in elite badminton players - Yuan, Shurui; Lu, Zepeng; Tan, Shiwen; Zhang, Zijie; Jing, Shiwei; Liu, Haoyang; Zhou, Zhihui; Bao, Dapeng (Frontiers in Physiology, 2025)
IntroductionThe aim of this study was to compare the effects of flywheel resistance training (FRT) and traditional resistance training (TRT) on deceleration and dynamic balance performance in elite badminton players.MethodsSeventeen elite male badminton players (age: 21.36 ± 2.10 years) volunteered to participate and were randomly assigned to either a flywheel resistance training group (FT: n = 8) or a traditional resistance training group (RT: n = 9). The FT group performed flywheel resistance training twice a week for 6 weeks, while the RT group participated in traditional resistance training for the same period. Deceleration and dynamic balance performance were assessed at baseline and following the intervention using the dynamic posture stability index (DPSI) test, 5-0-5 change of direction (COD) test, deceleration deficit (DD) test, and isometric mid-thigh pull (IMTP) test.Results and DiscussionRepeated-measures ANOVA revealed a significant time × group interaction for DPSI of both legs and peak force in the IMTP test (p < 0.05, partial η2 = 0.42–0.79), with better post-test performance compared to pre-test result in the FT group (ES = 0.30–2.10), and the improvements were higher than that of the RT group. No significant differences were observed in the DD test and COD test between FT and RT groups (p > 0.05); however, the magnitude of improvement in DD for the FT group (ES = 0.99) was greater than that of the RT group (ES = 0.52). This pilot study demonstrates that, compared to traditional resistance training, flywheel resistance training enhances deceleration performance and improves dynamic balance in elite badminton players.